DEVELOPMENT OF THE INTERRELATIONS OF TABLA AND KATHAK DANCE: AN ANALYTICAL STUDY (WITH SPECIAL REFERENCE TO THE COMPOSITIONS OF TABLA AND KATHAK DANCE): तबला एवं कथक नृत्‍य के अन्‍तर्सम्‍बन्‍धों का विकास : एक विश्‍लेषणात्‍मक अध्‍ययन (तबला एवं कथक नृत्‍य की रचनाओं के विशेष सन्‍दर्भ में) - Upadhyay, Dwijesh; Pant, Mukesh Chandra (International Journal of Research -GRANTHAALAYAH, 2017)
Both the tabla and the Kathak dances are rhythmic and hence there seems to be harmony among them. In the past, mridang was compatible with dance. But later when the dance included aspects such as adornment, miraculousness, pigmentation, etc., the solemn open and strongly relevant of Pakhawaj was unable to reconcile these aspects. In such a situation, the tabla instrument was used for association with Kathak dance, which is considered to be the sophisticated and developed form of mridang (pakhavajdha). The accompaniment of the tabla instrument proved successful in presenting almost all aspects of the dance accurately. Lucknow and the Banaras Gharana have played an important role in the association of Kathak dance. For the consistency of Kathak dance, the tabla players created and selected the characters, character groups, compositions according to the characters of the dance, compositions etc. The result of this is that with time, tabla playing material developed. Looking at the present form of Kathak.Dance also highlights the fact that tabla playing material has also played an important role in the development of Kathak.Nritya and its dance material. On this basis, both can be called complementary to each other. Music scholars also support the fact that while on one hand the tabla compositions have contributed to the enrichment of the Kathak dance, on the other hand various Kathakas have played an important role in the development of the tabla instrument. Based on the facts, the period of the Kathak dance and the revival of the tabla is considered to be the late 1700 century. It can be said that the tabla style and Kathak dance developed simultaneously. The tabla playing material; compositions and Kathak dance material; the development and expansion of compositions also continued to grow due to the tabla association with Kathak dance. The purpose of the proposed paper is to investigate and analyze the development of interrelations of the works of tabla and Kathak dance.